EFFECTIVENESS OF LINE MANAGERS TRAINING ON JOB PERFORMANCE AND JOB SATISFACTION - Mishra, Dr. Soma (The journal of contemporary issues in business and government, 2021)
Cutthroat labor force, business practices have developed to reflect financial seriousness in creating and holding capable employees. Associations are persistently looking for new answers for evaluate employee improvement. Preparing known as the nerve that gets the job done the need of smooth working of work which helps in improving job satisfaction among employee. The motivation behind this article paper is to survey the examination on the effectiveness of line managers preparing on job performance and job satisfaction.